Metastatic disease of the nervous system - Schiff, David, 1959-; Bent, Martin J. van den (Handbook of clinical neurology, 2018)
"Metastatic Disease of the Nervous System, Volume 149, begins with an overview of the impact and range of direct neoplastic involvement of the central and peripheral nervous system, comprehensively reviewing all aspects of brain metastases, from clinical, radiological and neuropathological manifestations, to the roles of surgery, radiation, systemic and palliative therapy in their management, and the complications of these interventions. The clinical manifestations, diagnosis and treatment of leptomeningeal, dural, spinal epidural and plexus metastases are also covered in detail."--Publisher's description